2015
DOI: 10.1108/jhom-02-2014-0038
|View full text |Cite
|
Sign up to set email alerts
|

New nurse transition: success through aligning multiple identities

Abstract: Although the concept of Fitting in and its relation to the attrition of novice nurses has been explored in global studies, that relationship has not yet been theorised as the dynamic alignment of multiple identities. Also, whilst most research around Fitting in, identity and retention has been conducted in western countries, little is known about these issues and their interrelationship in the context of Singapore. The study should inform decision making by healthcare organisations, nurse managers and nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(73 citation statements)
references
References 85 publications
2
50
0
21
Order By: Relevance
“…Recent studies have identified learning the names of colleagues and treating fitting in as a challenge are new insights into the approaches GNs use to fit in and eventually find their way into the ward milieu (Leong & Crossman, ; Mellor & Gregoric, ). Such persistence and individual conscious effort reflects the main theory and explains how GNs develop resilience, further contributing to their ability to adapt and fit in.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have identified learning the names of colleagues and treating fitting in as a challenge are new insights into the approaches GNs use to fit in and eventually find their way into the ward milieu (Leong & Crossman, ; Mellor & Gregoric, ). Such persistence and individual conscious effort reflects the main theory and explains how GNs develop resilience, further contributing to their ability to adapt and fit in.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on nurses’ socialization have identified two main challenges associated with the transition from school to practice. Firstly, newly graduated nurses experience stress and difficulties in performing their tasks due to a misfit between a previous desire to deliver nursing care and a reality framed by high workloads, interpersonal conflicts, feelings of being unprepared, and bureaucratic rules that the hospital requires nurses to follow (Leong & Crossman, ; Maben, Latter, & Clark, ; Unruh & Zhang, ). In line with these results, we tested whether the organizational resources for caring, that is, the efforts made by organizational members to help nurses deliver the best quality of care to patients, will impact their professional commitment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because entering the labor market is a major role transition for nurses, they inevitably question “who I am” as a professional. In the adjustment process leading to a successful socialization, new nurses negotiate a professional identity in such a way that their new professional reality fits with their self‐perceptions of being a nurse (Leong & Crossman, ).…”
mentioning
confidence: 99%
“…Constructivist grounded theory was adopted as an appropriate methodology to explore people's actions, experiences and views in relation to a phenomenon (Charmaz ). The study gave rise to a grounded theory reported elsewhere (Leong & Crossman ). This paper focuses on the concept of ‘tough love’ that arose through analysis.…”
Section: Methodsmentioning
confidence: 99%